DEAD-Box Helicase DDX25 Is a Negative Regulator of Type I Interferon Pathway and Facilitates RNA Virus Infection - Feng, Tingting; Sun, Ta; Li, Guanghao; Pan, Wen; Wang, Kezhen; Dai, Jianfeng (Frontiers in Cellular and Infection Microbiology, 2017)
Dengue is a mosquito-borne viral disease that rapidly spread in tropic and subtropic area in recent years. DEAD (Glu-Asp-Ala-Glu)-box RNA helicases have been reported to play important roles in viral infection, either as cytosolic sensors of viral nucleic acids or as essential host factors for the replication of different viruses. In this study, we reported that DDX25, a DEAD-box RNA helicase, plays a proviral role in DENV infection. The expression levels of DDX25 mRNA and protein were upregulated in DENV infected cells. During DENV infection, the intracellular viral loads were significantly lower in DDX25 silenced cells and higher in DDX25 overexpressed cells. Meanwhile, the expression level of type I interferon (IFN) was increased in DDX25 siRNA treated cells during viral infection. Consistent with the in vitro findings, the Ddx25-transgenic mice have an increased susceptibility to lethal vesicular stomatitis virus (VSV) virus challenge. The viremia was significantly higher while the anti-viral cytokine levels were lower in Ddx25-transgenic mice. Further, DDX25 modulated RIG-I signaling pathway and blocked IFNβ production, by interrupting IFN regulatory factor 3 (IRF3) and NFκB activation. Thus, DDX25 is a novel negative regulator of IFN pathway and facilitates RNA virus infection.